2021
DOI: 10.4103/ijo.ijo_1944_20
|View full text |Cite
|
Sign up to set email alerts
|

Capacity building for diabetic retinopathy screening by optometrists in India

Abstract: Purpose: The present study's objectives are 1) to describe a novel model of Diabetic Retinopathy Capacity Building (DRCB) for optometrists in the detection of diabetes-related retinal pathology in India and 2) to assess the outcomes of this model by comparing the ability of optometrists to detect these diseases using retinal photographs, vis-à-vis, a specialist ophthalmologist. Methods: The DRCB model for optometrists conducted between August 2016 and August 2018 includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…To decrease the burden of ophthalmologists, fellowship courses for capacity building of optometrists have been conducted and 870 optometrists were trained/certified in grading DR and STDR. [ 27 ]…”
Section: Screening For Drmentioning
confidence: 99%
See 2 more Smart Citations
“…To decrease the burden of ophthalmologists, fellowship courses for capacity building of optometrists have been conducted and 870 optometrists were trained/certified in grading DR and STDR. [ 27 ]…”
Section: Screening For Drmentioning
confidence: 99%
“…Physicians, optometrists, and vision technicians can receive training on DR screening and referral guidance. [ 24 27 ] The capacity building and certifications of these nonophthalmologists in DR and a comprehensive system of electronic medical records are important prerequisites for an ideal Tele-DR screening model. [ 27 ] Image transfer can be web based or satellite based.…”
Section: Screening For Drmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot project observed that the competencies of optometrists to screen for DR after a structured training were very good. [ 22 ] The study observed that the sensitivity and specificity for detection of any DR were 95% and 79%, respectively, and the sensitivity and specificity for VTDR were 88% and 90%, respectively. [ 21 ] These results are very encouraging and can open the door to adapting the English National Health Services protocols on screening and grading.…”
Section: Screening For Diabetic Retinopathymentioning
confidence: 99%
“…Rani and colleagues[ 12 ] including Ramasamy and colleagues,[ 13 ] in India, described a novel model of Diabetic Retinopathy Capacity Building for eight optometrists for screening of DR. This model which was set up for both hospital- and community-based service delivery included training and certification on the screening, and learning referral guidelines for DR.…”
Section: Capacity Building In Dr Screeningmentioning
confidence: 99%